Impact of Various Natural Feed Types on Water Quality on Silver Arowana (Osteo-glossum Bicirrhosum) - Kusumanti, Ima; Hendriana, Andri; Sholihah, Walidatush; Noviyanti, Inna; Marcelita, Faldiena (Green Publisher Indonesia, 2023)
The research was conducted to determine the relationship between water quality and body length of arowana fish by measuring several water parameters including temperature, pH, dissolved oxygen and ammonia. In relation to length growth, calculations on SR, SGR are also carried out using ANNOVA. Direct laboratory scale observations were carried out by providing different feeds, including bloodworms, maggot, crickets and live fish with the water source for cultivation activities being well water. The results of observations in the field show that the growth rate of fish in length is influenced by the type of feed given. Giving bloodworms has the most effective value, next to live fish, maggots and crickets. This type of feed also affects the quality of the water used. To maintain success in ornamental fish cultivation, it is recommended to use water efficiently through integrated fish cultivation. Checking the water regularly as well as training of farmers on good management practices and integration is needed to ensure good water quality.